Agriculture of the countries of the Western Balkans and European integrations - Tomić, Danilo; Ševarlić, Miladin M.; Tandir, Nataša (Applied Studies in Agribusiness and Commerce, 2012)
The paper presents the results of research of agriculture of the countries of the Western Balkans in the period of 2002–2009. Specifically, general economic (GDP per capita, share of agriculture in GDP, inflation rate, and unemployment rate), resource (share of arable land in the total utilized agricultural land, of employees in agriculture in the total number of employees, and of rural population in the total population), and value indicators (value added of agriculture in % of GDP, value added of agriculture per employee in agriculture, producers’ prices of wheat, corn, and bovine milk, share of agriculture in the values of export and import) were compared.